2008
DOI: 10.1007/s12298-008-0021-3
|View full text |Cite
|
Sign up to set email alerts
|

Salt-induced respiration in Bruguiera cylindrica — role in salt transport and protection against oxidative damage

Abstract: Leaves of Bruguiera cylindrica plants grown in the greenhouse and irrigated with fresh water (FW plants) and those from salt-adapted plants from the seacoast (SW plants) showed about 5-fold and 3-fold increase in respiration, respectively, when immersed in 4M NaCl solution. The increase in respiration was not due to dehydration effect of high salt concentration, since PEG-imposed dehydration stress to the leaves led to an inhibition of respiration rates in both FW and SW plants. The saltinduced increase in res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…high O 2 respiration rate) for their maintenance and growth. Previous studies reported that leaf and root respiration rates of mangrove species in the genera Avicennia , Bruguiera and Rhizophora lie within the range of 1–6 nmol O 2 or CO 2 g −1 s −1 ( Burchett et al , 1984 ; Hovenden et al , 1995 ; Lovelock et al , 2006 ; Atreya and Bhargava, 2008 ). This range is lower than that of terrestrial plants, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…high O 2 respiration rate) for their maintenance and growth. Previous studies reported that leaf and root respiration rates of mangrove species in the genera Avicennia , Bruguiera and Rhizophora lie within the range of 1–6 nmol O 2 or CO 2 g −1 s −1 ( Burchett et al , 1984 ; Hovenden et al , 1995 ; Lovelock et al , 2006 ; Atreya and Bhargava, 2008 ). This range is lower than that of terrestrial plants, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…ATP is needed in the processes of growth, and thus, ATP synthesis would also be increased for the growth enhancement stimulated by NaCl. Several previous studies have observed variances in mitochondrial respiration rate in some halophyte species under salt stress conditions (Atreya & Bhargava, 2008;Jacoby, Taylor & Millar, 2011). For example, recent proteomics-based studies have proposed an increase of mitochondrial ATP synthesis in several halophytes under salinity, such as Thellungiella halophila (Wang et al, 2013), Kandelia candel (Wang et al, 2014), and Puccinellia tenuiflora (Yu et al, 2011), through the observation of increased abundances of proteins involved in tricarboxylic acid (TCA) cycle, electron transport chain (ETC) complexes, and ATP synthases.…”
Section: Introductionmentioning
confidence: 95%